The Role of the Fund in the Poverty Reduction Strategy Process and Its Collaboration with Donors. (Policy Papers; Policy Paper ;, 2007)
This paper proposes an approach to making the MTS operational as it relates to the Fund's work in LICs that would define more precisely the Fund's responsibility and accountability in the PRSP and donor collaboration processes. The proposed activities are not 'new,' but represent an intensification of existing work and its extension to the all LICs as appropriate. This would help clarify expectations as to the Fund's role, and establish a consistent institutional approach to collaborating with donors and other stakeholders on the ground.